Evaluation of Andrographis paniculata Burm. f. extracts against Bemisia tabaci Gennadius - Najafabadi, Reza Tanha (2015)
Bemisia tabaci (Gennadius) (Hemiptera: Aleyrodidae) is one of the most destructive pests of vegetables and ornamental crops in the world. The development of resistance to most synthetic insecticides by this insect pest has necessitated a search for alternative methods of controlling it. Some botanical pesticides have been shown to provide satisfactory alternatives to chemical pesticides. Andrographis paniculata, an annual herb of the family Acanthaceae is primarily used for its medicinal properties, although insecticidal applications of this plant against insect pests of agricultural and medical importance have also been reported. This study aimed to evaluate the efficiency of various solvents in extracting the active compounds of A. paniculata, to determine the quality and quantity of the compounds and active ingredients in A. paniculata extract and to evaluate the toxicity of A. paniculata leaf extract against B. tabaci. Leaves of A. paniculata collected from Melaka, Malaysia were extracted with methanol, chloroform, and ethanol using Soxhlet extractor. Methanol was found to be the best solvent for the extraction of active compounds, especially andrographolide, from A. paniculata leaves. Chloroform gave the lowest yield of active compounds. Phytochemical screening of bioactive compounds in A. paniculata leaf extracts showed methanol extracts contained alkaloids, saponins, flavonoids, tannins, terpenoids and steroids. The levels of these bioactive compounds were generally low in chloroform and ethanol leafs extracts. The quantity andrographolide in methanolic A. paniculata leaf extract showed the highest amount (92.32 ppm) followed by ethanol (41.17 ppm) and chloroform (14.85 ppm). With regard to the toxicity of three solvent extracts (methanol, ethanol, and chloroform) of A. paniculata leaves against the adult and nymphal stages of B. tabaci, the most important finding was that A. paniculata leaf extract can be used as a bioinsecticide to control second instar nymphs and adults of B. tabaci. The LC50 values for methanol, chloroform and ethanol extracts of A. paniculata against second instar nymphs of B. tabaci were 39.48, 120.05, and 54.17 ppm, respectively. Among the three tested solvents, the crude methanol extract was found to have the most effective toxicity against second instar nymphs of B. tabaci. The toxicity of the three solvent extracts of A. paniculata was also tested against adults of B. tabaci after 96 hours of exposure. At this time point, the observed LC50 ranged from 43.68 ppm for the methanol extract to 172.7 ppm for the chloroform extract. The LC50 values for methanol, chloroform and ethanol extracts of A. paniculata against adult of B. tabaci were 43.68, 172.70, and 70.07 ppm, respectively. The larvicidal and adulticidal activity of A. paniculata against B. tabaci has not been previously studied in any detail, and this is the first report of its larvicidal and adulticidal activity against this pest.